Pengaruh Konformitas Teman Sebaya Dan Kontrol Diri Dengan Kepatuhan Terhadap Tata Tertib Sekolah Pada Siswa SMK X di Nganjuk: The Influence of Peer Conformity and Self-Control on Compliance with School Regulations Among Students of SMK X in Nganjuk - Dita Natasya Halimatussa Diyah; Eko Hardi Ansyah (Academia Open, 2025)
General Background: Student compliance with school regulations remains a central issue in educational psychology, particularly in understanding behavioral discipline among adolescents. Specific Background: School rule violations are frequently associated with limited self-regulation capacity and strong peer group pressure within the school environment. Knowledge Gap: Previous studies have examined self-control and peer conformity separately, yet limited empirical research has simultaneously analyzed their contribution to school rule compliance within a unified regression framework. Aims: This study aims to examine the relationship and contribution of self-control and peer conformity to students’ compliance with school regulations. Results: The findings indicate that self-control shows a significant positive association with compliance behavior, while peer conformity also contributes significantly. Simultaneously, both variables explain a meaningful proportion of variance in students’ adherence to school rules. Novelty: This study integrates internal regulatory factors and social conformity variables in a single predictive model within the context of secondary education. Implications: The results provide an empirical basis for school counselors and educators to design guidance programs focusing on strengthening self-regulation skills and managing peer group dynamics to foster disciplined behavior. Keywords: Self Control, Peer Conformity, School Rule Compliance, Student Discipline, Educational Psychology Key Findings Highlights Internal regulation capacity is strongly associated with adherence to institutional rules. Group alignment tendencies contribute to behavioral adjustment in academic settings. Combined predictive modeling explains substantial variance in disciplinary behavior.